Case report: Retrograde tracheal intubation using a guidewire for a difficult airway in a patient with severe facial burns - Arop M. D. Kual (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2020)
A technique of retrograde tracheal intubation is disclosed which employs a 7 Frx20cm central venous cannulation J-guidewire (from BIOMETRIX critical care solutions). The guidewire was inserted through the cricothyroid membrane and retrieved orally. An endotracheal tube was then passed over the guidewire under direct laryngoscopy.